2009
DOI: 10.1128/ec.00084-09
|View full text |Cite
|
Sign up to set email alerts
|

She3p Possesses a Novel Activity Required for ASH1 mRNA Localization in Saccharomyces cerevisiae

Abstract: Intracellular and intercellular polarity requires that specific proteins be sorted to discreet locations within and between cells. One mechanism for sorting proteins is through RNA localization. In Saccharomyces cerevisiae, ASH1 mRNA localizes to the distal tip of the bud, resulting in the asymmetric sorting of the transcriptional repressor Ash1p. ASH1 mRNA localization requires four cis-acting localization elements and the trans-acting factors Myo4p, She3p, and She2p. Myo4p is a type V myosin motor that funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…Although previous studies did not hint at a nuclear role of She3p [17],[18],[21][23],[36], this has not been tested directly. It is therefore a remaining possibility that the ternary complex also plays a functional role in the nucleus.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Although previous studies did not hint at a nuclear role of She3p [17],[18],[21][23],[36], this has not been tested directly. It is therefore a remaining possibility that the ternary complex also plays a functional role in the nucleus.…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies suggested that She3p acts only in the cytoplasm [17],[18],[21][23],[36]. However, this assumption had not been rigorously tested before.…”
Section: Discussionmentioning
confidence: 99%
“…She3p's binding site for Myo4p has been localized to the middle region of She3p (30), with a genetically determined upstream binding site for tER and a downstream binding site for zipcoded mRNP (29). Recently, the C-terminal region of She3p has also been reported to contain an RNA-binding site (25,31).…”
Section: Significancementioning
confidence: 99%
“…Instead, cargo binds via an "adaptor" protein, swi5p-dependent HO expression 3 protein (She3p) (7). Notably, the 425-residue-long She3p contains at least four binding modules that appear to be sequentially arranged along its primary structure (8)(9)(10)(11). Our recent composite crystal structure of a region of She3p (comprising residues showed that two She3p molecules form a pseudocoiled coil (6).…”
mentioning
confidence: 99%